RENEB Inter-Laboratory Comparison 2021: The Cytokinesis-Block Micronucleus Assay - Vral, A; Endesfelder, D; Balázs, J; Beinke, C; Cuceu Petrenci, C; Finot, F; Garty, G; Hadjiiska, L; Hristova, R; Ivanova, I; Lee, Y; Lumniczky, K; et al. (Radiation research, 2023)
The goal of the RENEB inter-laboratory comparison 2021 exercise was to simulate a large-scale radiation accident involving a network of biodosimetry labs. Labs were required to perform their analyses using different biodosimetric assays in triage mode scoring and to rapidly report estimated radiation doses to the organizing institution. This article reports the results obtained with the cytokinesis-block micronucleus assay. Three test samples were exposed to blinded doses of 0, 1.2 and 3.5 Gy X-ray doses (240 kVp, 13 mA, ∼75 keV, 1 Gy/min). These doses belong to 3 triage categories of clinical relevance: a low dose category, for no exposure or exposures inferior to 1 Gy, requiring no direct treatment of subjects; a medium dose category, with doses ranging from 1 to 2 Gy, and a high dose category, after exposure to doses higher than 2 Gy, with the two latter requiring increasing medical attention. After irradiation the test samples (no. 1, no. 2 and no. 3) were sent by the organizing laboratory to 14 centers participating in the micronucleus assay exercise. Laboratories were asked to setup micronucleus cultures and to perform the micronucleus assay in triage mode, scoring 500 binucleated cells manually, or 1,000 binucleated cells in automated/semi-automated mode. One laboratory received no blood samples, but scored pictures from another lab. Based on their calibration curves, laboratories had to provide estimates of the administered doses. The accuracy of the reported dose estimates was further analyzed by the micronucleus assay lead. The micronucleus assay allowed classification of samples in the corresponding clinical triage categories (low, medium, high dose category) in 88% of cases (manual scoring, 88%; semi-automated scoring, 100%; automated scoring, 73%). Agreement between scoring laboratories, assessed by calculating the Fleiss' kappa, was excellent (100%) for semi-automated scoring, good (83%) for manual scoring and poor (53%) for fully automated scoring. Correct classification into triage scoring dose intervals (reference dose ±0.5 Gy for doses ≤2.5 Gy, or reference dose ±1 Gy for doses >2.5 Gy), recommended for triage biodosimetry, was obtained in 79% of cases (manual scoring, 73%; semi-automated scoring, 100%; automated scoring, 67%). The percentage of dose estimates whose 95% confidence intervals included the reference dose was 58% (manual scoring, 48%; semiautomated scoring, 72%; automated scoring, 60%). For the irradiated samples no. 2 and no. 3, a systematic shift towards higher dose estimations was observed. This was also noticed with the other cytogenetic assays in this intercomparison exercise. Accuracy of the rapid triage modality could be maintained when the number of manually scored cells was scaled down to 200 binucleated cells. In conclusion, the micronucleus assay, preferably performed in a semi-automated or manual scoring mode, is a reliable technique to perform rapid biodosimetry analysis in large-scale radiation emergencies.